2021
DOI: 10.1016/j.jbusres.2020.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Branding the hotel industry: The effect of step-up versus step-down brand extensions

Abstract: This is a repository copy of Branding the hotel industry: the effect of step-up versus stepdown brand extensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 95 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Brand awareness is critically important due to its ability to differentiate one product from another in the competitive market [27,45]. In a scenario where a buyer is shopping for a product, brand awareness has been defined as the buyer's ability to identify and distinguish a brand within a given category with adequate detail and precision before making the purchase decision [46].…”
Section: Brand Awareness and Perceived Product Qualitymentioning
confidence: 99%
“…Brand awareness is critically important due to its ability to differentiate one product from another in the competitive market [27,45]. In a scenario where a buyer is shopping for a product, brand awareness has been defined as the buyer's ability to identify and distinguish a brand within a given category with adequate detail and precision before making the purchase decision [46].…”
Section: Brand Awareness and Perceived Product Qualitymentioning
confidence: 99%
“…Within hospitality, brand extensions are common. Research into consumers attitudes have found that positive attitudes towards the parent brand translate to positive attitudes towards the brand extension for a hotel if that brand extension is a stepdown, such as a limited-service extension from a full-service brand, then a step-up (Hultman et al 2021). Positive brand attitudes towards limited-service brands do not impact the attitudes towards full-service extensions.…”
Section: Select-service Hotelsmentioning
confidence: 99%
“…The literature identifies how satisfied customers are advantageous for the service providers; their satisfaction creates a ripple effect, which includes including loyalty to the service provider, engagement in positive word-of-mouth promotion, and paying premium prices (Ali et al 2017(Ali et al , 2016Dedeoglu and Demirer 2015;Amin et al 2013). Therefore, customer satisfaction has garnered considerable attention from both academics and practitioners (Hultman et al 2021;Assaker et al 2020;Hu et al 2009). In the tourism sector, these satisfactions interact with the type, variety, and quality of the services provided by a destination.…”
Section: Literature Reviewmentioning
confidence: 99%